Phytoremediation for Remediating Waste Water in Nandanpura Area, Jhansi (U. P.) - Neha Bansal; Chitra Gupta; Yash Sahini (International Journal of Pollution: Prevention & Control, 2025)
Water is the most essential commodity in our day to day life. It is unimaginable to survive without water. Access to clean water has emerged as a major issue globally. The Nandanpura area in Jhansi faces significant challenges with wastewater management, impacting both the environment and public health. Contamination of heavy metals such as Zinc, Copper, Cadmium etc have caused a lot of harmful diseases in human beings. In order to clean that waste water we need to use the process of Phytoremediation. Phytoremediation comprises various processes which includes: phytoextraction, rhizofiltration, phytostabilization, phytodegradation, and phytovolatilization. In phytoextraction, plants are utilized to remove heavy or toxic metals present in water. Similarly the rest of the processes are also used filter the contaminated ground and surface water. A range of studies is analyzed to offer an in-depth perspective on the applications and progress of phytoremediation. That results indicate that specific hyper accumulator plants effectively lower the levels of heavy metals and organic contaminants in wastewater. Additionally, the research explores the socio-economic advantages of implementing phytoremediation in Nandanpura, emphasizing its capacity to enhance environmental quality and community health. This investigation provides important insights into the practical use of phytoremediation technology, serving as a potential framework for other areas dealing with comparable waste water issues.
Keywords: Contamination; Copper; Nandanpura; Zinc; iron; phytoremediation; water